Do the kinematics and sensorimotor control of people with chronic non-specific neck pain differ from those of healthy individuals when assessed in an immersive virtual reality environment? A systematic review. (2nd November 2022) - Luc, Alexandre; Tamer, Stephany; Hage, Renaud; Detrembleur, Christine; Pitance, Laurent
Abstract: Objective: To compare the cervical kinematics and sensorimotor control (i.e., all the afferent, efferent, central integration, and processing components involved in maintaining joint stability) of people with chronic non-specific neck pain (CNSNP) to healthy controls, as assessed in an immersive virtual reality (VR) environment. Methods: A comprehensive electronic search was conducted in four databases to identify articles published from inception up until June 2022. The search terms were related to 'neck pain' and 'virtual reality'. Inclusion criteria were observational studies, written in English or French, including a majority of people with CNSNP (≥ 60%), and comparing the cervical kinematics or sensorimotor control between people with CNSNP and healthy controls in an immersive VR environment. Methodological quality was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Cross-Sectional Studies. The overall certainty of evidence was assessed using the GRADE approach. Results: Seven studies were included in the review. A narrative summary of results is provided for each study in relation to the outcomes assessed. Methodological quality was moderate to good. Cervical kinematics seemed to be altered in people with CNSNP compared with healthy controls, except for range of motion and response time. Sensorimotor control assessment showed inconsistent results. The certainty of evidence was very low for both kinematics and sensorimotor control. Conclusion: This systematic review provides very low certainty of evidence in favor of different kinematic neck patterns between healthy individuals and people with CNSNP when assessed in an immersive VR environment. No conclusion can be drawn concerning sensorimotor control.